Optimizing Multimodal Literacy in Elementary School Learning - Ngatman, Ngatman; Hidayah, Ratna; Suhartono, Suhartono; Susiani, Tri Saptuti; Salimi, Moh; Khasanah, Wahyu (Universitas Sebelas Maret, 2019)
This article is a theoretical review for describing multimodal literacy in elementary school learning. The exposure in this article is based on the application of multimodal literation. This paper relates to the pedagogic aspect of the implementation of multimodal literacy learning in the view of constructivism. Learning aims to prepare students for the era of the 4.0 Industrial Revolution. The idea of Literation has now changed because at this time it relates to digital content. Thus, multimodal literacy needs to be examined to explain the role of multimodal literacy in elementary school learning